MODEL PRO GAME BERBANTUAN WORDWALL DAN QUIZIZZ :STRATEGI MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN KERJASAMA - Taufik Arrahman; Diani Ayu Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was prompted by the low communication and collaboration skills of students in the Pancasila Education subject, caused by the use of inappropriate teaching models and methods, difficulty in retaining material, and the infrequent use of group discussions and presentations. To address these challenges, the PRO GAME model—integrating Problem-Based Learning, Game-Based Learning, and Team Games Tournament—was applied. The objective of the research was to enhance the communication and collaboration skills of fifth-grade students at SDN Kampung Baru.This Classroom Action Research (CAR) was conducted during the second semester of the 2024/2025 academic year, involving 27 students (14 boys and 13 girls). Qualitative data were collected through observations of students’ communication and collaboration, while quantitative data were gathered from written tests conducted individually and in groups. The results indicated a significant improvement: communication skills increased from 67% in the first meeting to 92% in the fourth, and collaboration skills rose from 63% to 95% over the same period.In conclusion, the implementation of the PRO GAME model effectively improved students' communication and collaboration skills. This research is recommended for school principals, teachers, and future researchers as a valuable reference for developing innovative and collaborative learning practices.